Leadership Rooted in Community-Based Local Wisdom Values - Hermawan, Hary; Nugroho, Dhimas Setyo; Afif, Fuadi; Wijayanti, Anita; Ahmad, Albattat; Valeri, Marco (Media Wisata, 2024)
Leadership in tourism villages that implement community-based tourism governance presents distinct challenges compared to company leadership. Tourism village leaders often encounter complex socio-cultural issues and conflicts, so leadership strategies and approaches are required to align with the local community's character and values. The research focuses on applying leadership that prioritizes local wisdom in community-based tourism management in tourism villages. The research method employed is qualitative, utilizing a grounded theory approach. The approach is used to dig the data from nine informants or participants. The participants in this research include heads of tourism villages who have successfully managed their villages for more than five years. The research results indicate that: (1) leadership based on local community wisdom values is a key element in ensuring the successful management and development of tourism villages. Effective leaders can mobilize and motivate the community, shift the mindsets, accommodate the volunteers, and optimize the community's social role. This leadership fosters a sustainable tourism village, positively impacting the economy and community welfare. (2) An inclusive, participative and deliberation-oriented approach becomes the leadership characteristic which prioritizes local wisdom values. This approach unites the community's vision and mission, listens to and accommodates aspirations, makes decisions democratically, and organizes active community participation effectively. (3) The success of leadership based on local wisdom values is measured not only by financial achievements but also by the ability to enhance community happiness, preserve the environment, ensure active community participation, and achieve predetermined goals. (4)The leadership model which prioritizes local wisdom values reflects a holistic and sustainable approach in tourism management. Local values and community participation are considered as the key success factors. This leadership illustrates the commitment to maintaining the local identity while creating sustainable benefits for the community and the surrounding environment.